2021
DOI: 10.1186/s12912-021-00704-1
|View full text |Cite
|
Sign up to set email alerts
|

Educating nursing students for cultural competence in emergencies: a randomized controlled trial

Abstract: Background Racial and ethnic minorities suffer significantly more than others in the wake of disasters. Despite the growing recognition of the importance of culturally competent health services, systematic cultural competence training in the medical education system is still scarce, especially in the field of emergency. The current study aimed to examine the effectiveness of an online culturally informed intervention for increasing cultural competence in emergencies among nursing students. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Remarkably, no interventional studies have investigated the impact of educational approaches such as the flipped classroom in cultural care training on critical cultural competence in mental health care settings. Consequently, this study relied on descriptive studies investigating the level of critical cultural competencies [12,18] and interventional and systematic review studies investigating the effects of various training methods on cultural competencies in healthcare providers in various settings [2,17,[19][20][21][22][23][24][25].…”
Section: Principal Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, no interventional studies have investigated the impact of educational approaches such as the flipped classroom in cultural care training on critical cultural competence in mental health care settings. Consequently, this study relied on descriptive studies investigating the level of critical cultural competencies [12,18] and interventional and systematic review studies investigating the effects of various training methods on cultural competencies in healthcare providers in various settings [2,17,[19][20][21][22][23][24][25].…”
Section: Principal Resultsmentioning
confidence: 99%
“…Consequently, the online training did not instill enough confidence in participants to apply the acquired techniques in real emergency environments. The researchers recommended further studies in this field using different methods and encompassing culturally diverse contexts [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the present study, several studies have reported that cultural competence training programs did not yield a significant impact on overall cultural competence or specific areas such as participants' attitudes and skills. These findings highlight the importance of carefully planning and organizing cultural education programs with the aim of effectively enhancing the development of cultural competence [40][41][42]. Furthermore, Tosun et al ( 2021) conducted a systematic review study that revealed a limited number of studies investigating the effectiveness of transcultural nursing education provided to nursing students.…”
Section: Discussionmentioning
confidence: 99%
“…As such, no noticeable difference was found in the results of this study compared to previous studies before COVID-19 outbreak. Cultural intelligence is a unique intelligence that helps us understand why some individuals are arguably more effective than others in an international environment [ 1 , 21 , 27 ]. Cultural education training online and offline programs can effectively increase the cultural competence of nursing students by increasing their cultural intelligence [ 22 ], help reduce the cultural difference between patients’ health and healthcare, and improve patient satisfaction and quality of health [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports of the COVID-19 outbreak showed that vulnerable population such as racial and ethnic minorities, including pregnant women, infants, and older adults, were at a higher risk of severe morbidity, complications, and death from the virus [ 1 ]. Globally, foreign citizens, particularly of Asian origin, have experienced discrimination and hostility related to the COVID-19 pandemic, and have received imbalanced medical services and insufficient economic resources [ 2 ].…”
Section: Introductionmentioning
confidence: 99%